Synergy routing and dynamic spectrum allocation in multi‐hop cognitive radio networks. Issue 2 (1st June 2014) - Zhu, Xiaorong; Zhu, Hongbo
Abstract : To maximise spectrum efficiency and channel capacity, both unused (white) and underused (grey) spectral regions need to be exploited. The authors propose a distributed and localised algorithm for joint opportunistic routing and spectrum allocation for multi‐hop cognitive radio networks, and design a synergy routing, a utility‐based routing scheme that achieves synergistic cognitive radio benefits of overlay and underlay techniques and simultaneously maximises spectrum efficiency. The synergy routing opportunistically calculates the next hop according to the spectrum dynamics and residual energy of candidate relays and harvests the benefits from the cooperation of underlay and overlay spectrum. Simulation results indicate that our synergy prototype improves delay and throughput performance, while maintaining the autonomy and heterogeneity of individual underlay and overlay networks.